2021
DOI: 10.2147/cmar.s298918
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PCAT18 Promotes Non-Small Cell Lung Cancer Progression by Sponging miR-4319

Abstract: Introduction NSCLC (non-small cell lung cancer), the most common type of human cancer, is a main cause of cancer-associated mortality. Accumulating evidence has confirmed that long non-coding RNAs serve crucial roles in NSCLC development. Methods The PCAT18 expression in NSCLC tissues and cell lines were evaluated by reverse transcription-quantitative PCR. Cell Counting Kit-8 assays, colony formation study, wound healing assays and transwell invasion assays, and tumor x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…S3A and B ). Among these genes, IL17REL, KLRC2, MGAM2 [ 51 ], and XAGE1B [ 52 ] are associated with the immune response and immunotherapy, whereas PCAT18, TUSC8, and GPR31 have been reported to be therapeutic targets in tumors [ [53] , [54] , [55] ]. Additionally, overall survival analysis of these genes in CS3 patients found that C11orf86 and LINC02539 were significantly correlated with prognosis in patients with the CS3 subtype, whereas IL17REL, KLRC2, INSM1, and XAGE1B were potential prognostic factors ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3A and B ). Among these genes, IL17REL, KLRC2, MGAM2 [ 51 ], and XAGE1B [ 52 ] are associated with the immune response and immunotherapy, whereas PCAT18, TUSC8, and GPR31 have been reported to be therapeutic targets in tumors [ [53] , [54] , [55] ]. Additionally, overall survival analysis of these genes in CS3 patients found that C11orf86 and LINC02539 were significantly correlated with prognosis in patients with the CS3 subtype, whereas IL17REL, KLRC2, INSM1, and XAGE1B were potential prognostic factors ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ENKUR was shown to suppress malignant activities of hepatocellular carcinoma by modulating the β‐catenin/c‐Jun/MYH9/USP7/c‐Myc axis (Hou et al, 2022). SDHAP1 was involved in the proliferation, migration, and invasion of NSCLC (L. He et al, 2021). PTGIS and EARS2 were demonstrated to regulate colon cancer metastasis (Cui et al, 2021; Sun et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…SDHAP1 was involved in the proliferation, migration, and invasion of NSCLC (L. He et al, 2021). PTGIS and EARS2 were demonstrated to regulate colon cancer metastasis (Cui et al, 2021;Sun et al, 2012).…”
Section: Enkd1 Expression Correlates With the Expression Of Various R...mentioning
confidence: 99%
“…[ 10 ] LncRNA PCAT18 contributed to the NSCLC progression by sponging miR‐4319. [ 11 ] The miR‐17‐92a‐1 cluster host gene (MIR17HG) is a newly identified lncRNA located at 13q31.3 of the human chromosome. [ 12 ] Accumulating evidence indicated that MIR17HG served essential roles in human cancer.…”
Section: Introductionmentioning
confidence: 99%